Antonio’s Inwardness and Foreclosure in The Merchant of Venice - Ludwig, Carlos Roberto (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2022)
This article discusses the ambiguous representation of the merchant Antonio in William Shakespeare’s The Merchant of Venice. Antonio’s relationship to his father figure is projected through the hatred and sadness in Shylock’s figure. However, Antonio's father figure is completely absent in the play. Thus, his inexplicable anger towards Shylock may reveal primitive feelings towards his father figure. His masochistic desire and fear of castration, which can potentially be fulfilled by Shylock, increase his anxiety to his father figure. He accepts the idea of castration and imagines himself a castrated ram. However, the cause of such anxiety is constantly denied by Antonio, but projected into the play’s texture in verbal slips and contradictions. Thus, the other characters are depicted as Antonio’s correlate figures, mirroring similar feelings felt by him.